Nimble Tongues Studies in Literary Translingualism - Kellman, Steven G. (Comparative Cultural Studies, 2020)
Nimble Tongues is a collection of essays that continues Steven G. Kellman's work in the fertile field of translingualism, focusing on the phenomenon of switching languages. A series of investigations and reflections rather than a single thesis, the collection is perhaps more akin in its aims-if not accomplishment-to George Steiner's Extraterritorial: Papers on Literature and the Language Revolution or Umberto Eco's Travels in Hyperreality. Topics covered include the significance of translingualism; translation and its challenges; immigrant memoirs; the autobiographies that Ariel Dorfman wrote in English and Spanish, respectively; the only feature film ever made in Esperanto; Francesca Marciano, an Italian who writes in English; Jhumpa Lahiri, who has abandoned English for Italian; Ilan Stavans, a prominent translingual author and scholar; Hugo Hamilton, a writer who grew up torn among Irish, German, and English; Antonio Ruiz-Camacho, a Mexican who writes in English; and the Universal Declaration of Human Rights as a multilingual text.